Microorganisms diversity in coffee grown close to the Lake Furnas - Compri, Larissa; Florentino, Ligiane Aparecida; Veiga, Rosane Micaela; Silva, Adriano Bortolotti; Miranda, José Messias (Coffee Science - ISSN 1984-3909, 2016)
Several coffee farms in southern Minas Gerais have their crops to the shores of Lake Furnas. The aim of this study was to analyze the influence of Furnas Lake proximity on diversity of microorganisms and sensory quality coffee and physics. Fruits and coffee beans were collected in Alfenas, located on the shores of Lake Furnas, and Cabo Verde, whose municipality is not bathed in this lake. The isolation of organisms was accomplished by plating technique directly on selective media. The greatest diversity of microorganisms was verified in Alfenas municipality of samples. By cup test samples obtained in both two locations were classified as stiff drink.